Contribution of changes in demography and in the risk factors to the predicted pattern of cancer mortality among Spanish women by 2022. (February 2016) - Clèries, Ramon; Buxó, Maria; Martínez, José M.; Espinàs, Josep A.; Dyba, Tadeusz; Borràs, Josep M.
Highlights: The burden of cancer mortality among Spanish women is predicted to change during 2018–2022. Colorectal cancer could surpass breast cancer as the leading cause of cancer mortality. Lung cancer is predicted to overtake breast cancer among women aged 50–69 years. Death rates from pancreatic cancer are continuing to increase among women aged 50 and older. Demographic shifts might drive the burden of colorectal cancer mortality whereas changes in the risk factors might have the largest contribution to the burden of lung and pancreatic cancer. Abstract: Background: Changes in the burden of cancer mortality are expected to be observed among Spanish women. We predict those changes, in Spain, for breast cancer (BC), colorectal cancer (CRC), lung cancer (LC) and pancreatic cancer (PC) from 2013 to 2022. Methods: Bayesian age–period–cohort modeling was used to perform projections of the cancer burden in 2013–2022, extrapolating the trend of cancer mortality data from 1998 to 2012. We assessed the time trends of the crude rates (CRs) during 1998–2012, and compared the number of cancer deaths between the periods 2008–2012 and 2018–2022 to assess the contribution of demographic changes and changes in the risk factors for cancer. Results: During 1998–2012, CRs of cancer decreased for BC (0.3% per year) and increased for LC (4.7%), PC (2%) and CRC (0.7%). During 2013–2022, CRs might level off for CRC, whereas the time trends for the remaining cancers might continue at a similar pace. During 2018–2022, BC could be surpassed by CRC as the most frequent cause of cancer mortality among Spanish women, whereas LC could be the most common cause of cancer mortality among women aged 50–69 years (N/year = 1960 for BC versus N/year = 1981 for LC). Comparing 2018–2022 and 1998–2012, changes in the risk factors for cancer could contribute 37.93% and 18.36% to the burden of LC and PC, respectively, and demographic shifts – mainly due to ageing (19.27%) – will drive the burden of CRC. Conclusions: During 2018–2022, demographic changes (ageing) and changes in risk factors could have a different impact on the lifetime risk of cancer among Spanish women.